Simulation of the impact of solar radiation intensity on the performance of economical solar water desalination still in Semnan province. (December 2021) - Hemmat Esfe, Mohammad; Esfandeh, Saeed; Kamyab, Mohammad Hassan; Toghraie, Davood
Abstract: Semnan province with a total area of 97000 km 2 is the sixth biggest province in Iran. The evaporation rate in this province is high and can be. The index of the urban and rural water networks in this province is much higher than the global average, but according to the goals set for water supply to all people in all cities and villages, using new technologies is an effective way. High potential evaporation intensity in Semnan province, which reaches 1000-3000 (mm) per year, can be converted from a threat to an opportunity by using it as a new source of energy for a sustainable safe drinking water supply. In order to use of evaporation capacity, in this paper the impact of solar radiation intensity on the performance of single-slope solar still is investigated. The solar radiative flux depends on geographical location, season, and time. In this study, the dimension and temperature of the basin are constant and the effect of radiation intensity on water productivity of solar stills is investigated as a function of time, month (April) and location (Semnan province). The accuracy of the numerical method has been evaluated using different models and experimental data for the average Nusselt number on water surface and production rate of water. Results also indicate that the variation trends for radiation intensity are similar to the production rate. The maximum water production rate belongs to 12 o'clock with a 5.6% increase in comparison with 7:00 a.m., which has the lowest evaporation rate in the bell shaped curve.